3ax-2=5ax-1

Simple and best practice solution for 3ax-2=5ax-1 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3ax-2=5ax-1 equation:


Simplifying
3ax + -2 = 5ax + -1

Reorder the terms:
-2 + 3ax = 5ax + -1

Reorder the terms:
-2 + 3ax = -1 + 5ax

Solving
-2 + 3ax = -1 + 5ax

Solving for variable 'a'.

Move all terms containing a to the left, all other terms to the right.

Add '-5ax' to each side of the equation.
-2 + 3ax + -5ax = -1 + 5ax + -5ax

Combine like terms: 3ax + -5ax = -2ax
-2 + -2ax = -1 + 5ax + -5ax

Combine like terms: 5ax + -5ax = 0
-2 + -2ax = -1 + 0
-2 + -2ax = -1

Add '2' to each side of the equation.
-2 + 2 + -2ax = -1 + 2

Combine like terms: -2 + 2 = 0
0 + -2ax = -1 + 2
-2ax = -1 + 2

Combine like terms: -1 + 2 = 1
-2ax = 1

Divide each side by '-2x'.
a = -0.5x-1

Simplifying
a = -0.5x-1

See similar equations:

| -3d+5+d15= | | f(x)=6xln(2x)-6x | | 11=-5g-2 | | (3x-1)(10x-3)=0 | | 3x+3(6x-12)=132 | | 3r-4rs+2s= | | 0.07=56 | | 72=9g | | 2X-21+3X-34=180 | | -4(5x+2)+3(x-3)= | | 2w-3(3w+5)=3w+5 | | -8x-5y=15 | | 35-19=3(x-3) | | ?(2x-4)+5=-?(x+1) | | 3x^3+13x^2-16=0 | | 48x^2-16x-20=0 | | -138-6(6b-7)= | | 2n-1=-11 | | 4x+8y=52 | | 3n-8=-20 | | 4x-10=12+4(x+8) | | 2-c=29 | | ?(2x-4)=-?(x+1) | | 4t-1=5(t+5) | | 3x=7x+20 | | 5(6+3r)+7127= | | 13mn-5nm+2mn= | | 6+5ln(2x-1)=21 | | 2x+14=8-3y | | x^2-15x+(56.25)=8 | | 1.6=2y+7.8 | | 4-n=6 |

Equations solver categories